2021
DOI: 10.1016/j.vas.2021.100188
|View full text |Cite
|
Sign up to set email alerts
|

Serological detection and genetic characterization of foot-and-mouth disease virus from cattle in northern sudan, 2016‑2018

Abstract: Highlights Clinical FMD was confirmed as serotype O of an unnamed lineage within the topotype East Africa 3 (EA3). Unlike Western, Eastern, Central and Southern Sudan, no predominance of serotype O antibodies was detected in Northern Sudan. Sero-prevalence estimates of serotype-specific antibodies ranged between 15.4% (serotype A) in the River Nile State to 3.4% (serotype SAT2) in the Northern State.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Also, positive and negative serum and milk samples were used for rapid test GNPS-LFT validation as shown in Table 3 and Fig. 2 and this result is in agreement with ( 38 ). Detection of FMDV antigen and/or antibody in serum and milk samples collected from naturally infected animals during the FMD outbreak) by GNPT-LFT compared to different assays (IC, SAT-SPA, and 3ABC-ELISA) revealed that the GNPs-LFT gave nearly the same results as the assays, as shown in Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Also, positive and negative serum and milk samples were used for rapid test GNPS-LFT validation as shown in Table 3 and Fig. 2 and this result is in agreement with ( 38 ). Detection of FMDV antigen and/or antibody in serum and milk samples collected from naturally infected animals during the FMD outbreak) by GNPT-LFT compared to different assays (IC, SAT-SPA, and 3ABC-ELISA) revealed that the GNPs-LFT gave nearly the same results as the assays, as shown in Fig.…”
Section: Discussionsupporting
confidence: 80%
“…GNPs-LFT serves as an alternative means of sample testing and helps in the implementation of appropriate control measures. However, with the introduction of FMDV of different serotypes to different regions, future efforts will focus on the failure of the GNPs-LFT for detection of FMDV in nearly 15%–20% of ELISA positive samples, and this observation is agreed with ( 36 38 ).…”
Section: Discussionmentioning
confidence: 82%
“…In our study, only serotype O, EA-3 topotype was detected using serotype-specific primers. Serotype O is the most prevalent serotype worldwide [ 30 ], alone or with other serotypes, and is responsible for several outbreaks in Egypt [ 18 , 42 , 59 ] and other countries, such as Argentina [ 60 ], Sri Lanka [ 61 ], India [ 62 ] and neighboring countries as Palestine, Libya [ 3 , 18 , 63 ] and Sudan [ 59 , 64 ]. Isolation of FMDV serotype O, EA-3 topotype from Egyptian farms during this FMDV outbreak, however controlling this serotype (O) and serotype A by vaccination in Egypt [ 44 ], indicating that the FMDV constitutes an endemic severe health problem for the livestock industry in Egypt [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased virulence strains among cattle and buffalo in Egypt could be attributed to the introduction of new viral strains through uncontrolled transboundary movements of animals [ 18 , 64 , 77 ]. The sequence and phylogenetic analyses revealed the presence of older isolates and vaccinal strains in separate clusters and subclades far away from the present isolate and recently isolated reference strain, which was grouped in one cluster.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the genetic diversity of ribonucleic acid (RNA) viruses such as FMDV results from the error-prone replication process of the RNA-dependent RNA polymerase (RdRp), large population diversity, and high replication rate [16] as well as recombination [17][18][19][20]. RNA viruses such as FMDV, without the involvement of any external driving force, use positive selection mechanisms termed broadly diversifying selection.…”
Section: The Causes Of Fmd Virus Diversitymentioning
confidence: 99%